2012
DOI: 10.1038/ki.2012.191
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K intake and status are low in hemodialysis patients

Abstract: Vitamin K is essential for the activity of γ-carboxyglutamate (Gla)-proteins including matrix Gla28 protein and osteocalcin; an inhibitor of vascular calcification and a bone matrix protein, respectively. Insufficient vitamin K intake leads to the production of non-carboxylated, inactive proteins and this could contribute to the high risk of vascular calcification in hemodialysis patients. To help resolve this, we measured vitamin K(1) and K(2) intake (4-day food record), and the vitamin K status in 40 hemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
173
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(183 citation statements)
references
References 27 publications
9
173
1
Order By: Relevance
“…Additionally, patients treated with VKA for prolonged time (greater than 1 year) have a higher risk of vascular calcifications [44,47] and increased arterial stiffness [48] , two major risk factors for cardiovascular mortality [49] , independent of other well-known risk factors including serum levels of bone markers. Such effects are similar to those observed in patients with vitamin K deficiency [50] and might be particularly strong in HD patients for whom the activity of Matrix γ-carboxyglutamate proteins, a group of vitamin K-dependent proteins inhibiting vascular mineral deposition, is severely hampered [29,47,48] . Our design cannot completely rule out the alternative hypothesis that residual bias by indication affected our risk estimates.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Additionally, patients treated with VKA for prolonged time (greater than 1 year) have a higher risk of vascular calcifications [44,47] and increased arterial stiffness [48] , two major risk factors for cardiovascular mortality [49] , independent of other well-known risk factors including serum levels of bone markers. Such effects are similar to those observed in patients with vitamin K deficiency [50] and might be particularly strong in HD patients for whom the activity of Matrix γ-carboxyglutamate proteins, a group of vitamin K-dependent proteins inhibiting vascular mineral deposition, is severely hampered [29,47,48] . Our design cannot completely rule out the alternative hypothesis that residual bias by indication affected our risk estimates.…”
Section: Discussionsupporting
confidence: 55%
“…Among AF patients without ESRD, warfarin prevents mortality and strongly reduces the risk of stroke [40] . Due to platelet dysfunction, reduced dietary vitamin K intake, altered bioavailability, higher susceptibility to vascular calcifications, HD patients may have a less favorable riskbenefit profile compared to non-ESRD patients with AF [26][27][28][29] . Epidemiological studies seem to corroborate such hypothesis: a recent meta-analysis showed that VKA does not reduce the risk of stroke and increase the risk of bleeding among ESRD patients with AF [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, increased calcification of aortic valves was observed in patients receiving preoperative VKAs relative to non-treated patients [34,35]. Chronic kidney disease (CKD) patients, a population with a high prevalence of cardiovascular mortality and vascular calcifications, have been associated with subclinical vitamin K deficiency [35,36]. In a CKD rat model, warfarin treatments increased vascular calcification while high dietary vitamin K1 increased vitamin K tissue concentrations and attenuated vascular calcification [37].…”
Section: Vitamin K-antagonists As Indicators Of Vitamin K Importance mentioning
confidence: 99%
“…The predominant dietary form of vitamin K in the USA, Europe, and most Western countries is phylloquinone, while the major form in Japan is menaquinones, especially menaquinone 7 (MK-7), which is a component of natto (3). Few data are available on vitamin K intake both in the general population and in chronic kidney disease patients (32). Recently, we evaluated the dietary intake of PK in a cohort of patients undergoing hemodialysis (33).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%